2021
DOI: 10.1016/j.aquaculture.2020.735729
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS as a promising tool to assess potential virulence of Vibrio tapetis isolates

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The time‐to‐identification can be decreased when compared to other bacteriologic techniques such as biochemical profiling or immunofluorescent assays, and this is particularly true for slow‐growing organisms like R. salmoninarum . Its application and feasibility in the identification of bacterial species of freshwater and seawater finfish and crustacean species have been extensively reported (Bronzato et al, 2018; Jung‐Schroers et al, 2018; 2019; Moussa et al, 2021; Nhu et al, 2016; Ojasanya et al, 2022; Pečur Kazazić et al, 2019; Rahmani et al, 2021; Yolanda et al, 2019), including for the fastidious salmonid pathogens R. salmoninarum (Jansson et al, 2020), Flavobacterium species (Fernández‐Álvarez et al, 2018; Jansson et al, 2020), Piscirickettsia salmonis (Olate et al, 2016) and Tenacibaculum maritimum (Fernández‐Álvarez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The time‐to‐identification can be decreased when compared to other bacteriologic techniques such as biochemical profiling or immunofluorescent assays, and this is particularly true for slow‐growing organisms like R. salmoninarum . Its application and feasibility in the identification of bacterial species of freshwater and seawater finfish and crustacean species have been extensively reported (Bronzato et al, 2018; Jung‐Schroers et al, 2018; 2019; Moussa et al, 2021; Nhu et al, 2016; Ojasanya et al, 2022; Pečur Kazazić et al, 2019; Rahmani et al, 2021; Yolanda et al, 2019), including for the fastidious salmonid pathogens R. salmoninarum (Jansson et al, 2020), Flavobacterium species (Fernández‐Álvarez et al, 2018; Jansson et al, 2020), Piscirickettsia salmonis (Olate et al, 2016) and Tenacibaculum maritimum (Fernández‐Álvarez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Three sub-species have been described for V. aestuarianus aestuarianus , V. aestuarianus francensis associated with cupped oyster diseases, and V. aestuarianus cardii , associated with cockle diseases (Garcia et al 2021 ). Further analysis could be applied to sub-type species or to discriminate between pathogenic and non-pathogenic strains, e.g., the “MALDI-TOF-MS Multi Peak Shift Typing approach,” highlighting a link between a peak shift in the mass spectra and the associated polymorphism in the genomic sequence (Bridel et al 2020 ; Rahmani et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low et al (2014) reported the identification of V. alginolyticus from Epinephelus fuscoguttatus (brown-marbled grouper) using MALDI TOF. Additionally, Rahmani et al (2021) also came to the conclusion that V. tapetis isolated from Manila clams, were found as pathogenic based on the protein profiles which demonstrated the presence of a virulence gene. V. parahaemolyticus, the causative agent of However, there are some limitations to take into account.…”
Section: Vibrio Spp and Other Fish Pathogensmentioning
confidence: 97%